Papel protetor do gene humano APOE4 em camundongos transgênicos submetidos pela desnutrição e infecção pelo Criptosporidium parvum - Azevedo, Orleâncio Gomes Ripardo de (2012)
The vicious cycle of enteric infections and malnutrition during childhood is a major public health problem with devastating consequences and its effects are not fully elucidated. Oria and colleagues in 2005 showed that children with heavy diarrhea burdens when carrying the APOE 4 gene had a better cognitive performance. The aim of this study was to evaluate the protective role of APOE 4 gene in C57BL6J mice challenged by malnutrition induced by a 2% protein diet and intestinal infection caused by Cryptosporidium parvum. We used male C57BL6J mice weighing in average 14g, challenged by malnutrition for a period of 14 days compound with 7 days of C. parvum infection through a single dose of 107 oocysts given by gavage. Study animals were separated according to their genotype, as following: wild-type, APOE knock-out, APOE 3/3 (carriers of the human APOE 3 gene) and APOE 4/4 (carriers of human APOE 4 gene). Control animals received PBS by gavage. Body weight of the animals was monitored daily. Mice were sacrificed in CO2 chamber with posterior cervical dislocation after 14 days from the beginning of the protocol. During the post-infection period, stools samples were collected from the infected mice every other day for real time quantitative PCR (qPCR) assays in order to quantify C. parvum oocysts released in the stools. Ileal samples were immediately frozen in liquid nitrogen and then stored in a freezer at -80°C for molecular analyses. Other samples were fixed in buffered paraformaldehyde (4%) for histological processing. Morphometric parameters were evaluated for villus height and crypt depth in the ileal segments. For detection of a proinflammatory cytokine panel (IL- 1β, IFN-γ, TNF-α, and IL-17), we used the multiplex assay (Luminex xMAP). In addition by qPCR, the cationic amino acid transporter (CAT-1), arginase 1, iNOS, and TLR9 were assessed. Regarding weight, we found a greater adaptation to weight loss in APOE 4 animals in the 2nd and 3rd days of malnutrition (p<0.05) and in the postinfection time there was a significant difference on the 2nd day (p<0.05) compared to all groups. In the morphometric analyses, we found villus blunting and crypt disorganization in APOE knockout mice. We found APOE 4 protection against these alterations compared to all groups (p<0.05). The C. parvum oocyst shedding data indicate an increase in the pro-inflammatory state and anti-parasitic effects seen in the APOE Ko and APOE 4/4 mice, as confirmed by a significant reduction of the C. parvum released in the stools. In addition, we found increased levels of the intestinal pro-inflammatory cytokine (IL-1β) (p<0.05) in the APOE Ko when compared with APOE3/3 and APOE4/4, higher levels of IFN-γ (p<0.05) when compared with wild-type and undernourished APOE Ko controls. The APOE Ko undernourished mice have increased intestinal levels of IL-17 compared with APOE Ko undernourished infected mice. qPCR data demonstrate that the presence of the APOE4 genotype in mice increased the primary transcripts of CAT-1 and arginase 1 in comparison to wild types, APOE Ko, and APOE 3/3 (p<0.05). Furtermore, APOE knockout mice had higher iNOS expression in comparison to all groups (p<0.05). The APOE 4 mice showed significant increase in the expression of TLR9 mRNA in the ileum when compared to APOE Ko mice (p<0.05). Altogether we concluded that the APOE 4 carriers have a balanced pro-inflammatory response, benefiting the C. parvum control, as seen by reduction of the parasite DNA released in the stools, and by improvements in the growth rates in the mice challenged malnutrition/infection, suggesting that the hosts carrying the APOE4 genotype have a better protection against the intestinal alterations induced by the compound challenge of C. parvum infection and malnutrition.